Pembuatan Karya Inovasi Ecobrick Mahasiswa KKNT 32 Universitas Nusantara PGRI Kediri di SDN Pojok 2 - Permana, Erwin Putera; Winarto, Jotter Fikri; Wardani, Saylendra Arga; Yugianta, Laurentius Hendri; Airlangga, Muhammad Adam; Putra, Dymas Ajie Pramana; Mardian, Wannu Rizki Dicky; Yahya, Wildan Ramadhani; Robert, Davin Zainur; Wardhani, Aurel Fransisca Kusuma; Rahardian, Muchamad Gilang Nauri; Muzaki, Muhammad Rezai; Azzaria, Cinta; Pripinda, Ayuneira Dega; Sindhikara, Legaspie Aura (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2025)
Innovation in plastic waste management has become one of the key solutions to addressing the increasingly urgent environmental issues. One of the efforts undertaken by KKNT 32 UNP Kediri students is the creation of Ecobricks at SDN 2 Pojok. This initiative aims to introduce an innovation that integrates plastic waste recycling into environmentally friendly building materials. An Ecobrick is a plastic bottle filled with compacted non-organic waste, which can be used as an alternative material in construction. This activity involves students, teachers, and the surrounding community in the process of making Ecobricks and implementing them to improve the school environment. The methods used in this program include socialization, material collection, Ecobrick production, and evaluation of the results. Through this program, students' awareness of the importance of waste management increases, while also making a tangible contribution to environmental preservation. This innovative project not only provides a solution to plastic waste problems but also educates the younger generation to be more concerned about environmental sustainability.